EFEKTIFITAS MIKROORGANISME LOKAL (MOL) TAPE SEBAGAI AKTIVATOR PEMBUATAN KOMPOS - Panjaitan, Heri (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
Target conducted by this research is to know Efectivity of Local Microorganism activator (MOL) Tape to time depth forming of organic garbage compost. This research type represented experiment using desain